Financial cryptography and data security : 19th International Conference, FC 2015, San Juan, Puerto Rico, January 26-30, 2015, Revised selected papers /: 19th International Conference, FC 2015, San Juan, Puerto Rico, January 26-30, 2015, Revised selected papers. (2015) - Unknown
No abstract available